Outcomes of AIDS policy-based interventions in the Further Education and Training Sector - Moiloa, Mohlalefi Edwin (My University, 2017)
A number of AIDS prevention interventions have been developed and implemented nationwide to counter the nerve-racking onslaught of HIV/AIDS, which continues to pose a grave danger to economic and social development. However, worsening conditions of the epidemic suggest that the political and social contexts within which proposed campaigns have been launched, are not fertile enough for the AIDS policy-based interventions to yield the outcomes sought and consequently the desired impacts (Schneider and Stein, 2001). The escalating behaviour associated with the risk of acquiring HIV does not only undermine prevention measures in place, but also the ability of those implementing strategies to effectively influence behaviour change among the youth (Moodley and Philips, 2011). The study sought to evaluate the outcomes of AIDS policy-based interventions, focusing its attention on a specific sector consisting of individuals at the peak of sexual activity. Data were collected through an anonymous self-administered questionnaire which elicited information on the outcome measures: AIDS-related knowledge, risk perceptions and behaviour associated with the risk of infection. 518 levels 3 and 4 students registered with South West Gauteng College and Western College and fulfilling inclusion criteria of 18 and above years participated in the study. The results proved the intervention successful in one outcome measure―knowledge of AIDS―in which the FET students’ levels were sub optimal (less than 95%). On two other measures, the results were not consistent with the theory of change for the intervention, suggesting availability of missing elements in the logical sequence of the results chain and its accompanying results framework, and therefore producing unintended outcomes. Relatively low risk perceptions and high levels of unhealthy life-styles as well as risky sexual habits were discovered from the FET students’ responses. The inability of the AIDS policy-based interventions at outcome level reflected almost no possibilities of it arriving at the stated results (impact level).
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand March 2016